Hydroxylated Polyfunctionalized Benzo[c]coumarins by an Organocatalyzed Tandem 1,4-Conjugate Addition, Decarboxylation and Aromatization Reaction - Talhi, Oualid; Makhloufi-Chebli, Malika; Pinto, Diana C. G. A.; Hamdi, Maamar; Silva, Artur M. S. (Synlett, 2013)
Novel hydroxylated polyfunctionalized benzo[c]coumarins were synthesized by a new one-pot reaction of an unprotected monohydroxy-3-(acetoacetyl)coumarin as an active methylene Michael donor with 4-oxo-4H-chromene-3-carboxylic acid as a Michael acceptor in the presence of a catalytic amount of 4-pyrrolidin-1-ylpyridine. An organobase-catalyzed tandem 1,4-conjugate addition, decarboxylation and aromatization reaction mechanism is proposed.
Keywords: heterocycles; polycycles; ketones; tandem reactions; addition reactions; catalysis